Supported Lipid Bilayers for the Generation of Dynamic Cell–Material Interfaces. Issue 18 (17th November 2015) - van Weerd, Jasper; Karperien, Marcel; Jonkheijm, Pascal
Abstract : Supported lipid bilayers (SLB) offer unique possibilities for studying cellular membranes and have been used as a synthetic architecture to interact with cells. Here, the state‐of‐the‐art in SLB‐based technology is presented. The fabrication, analysis, characteristics and modification of SLBs are described in great detail. Numerous strategies to form SLBs on different substrates, and the means to patteren them, are described. The use of SLBs as model membranes for the study of membrane organization and membrane processes in vitro is highlighted. In addition, the use of SLBs as a substratum for cell analysis is presented, with discrimination between cell–cell and cell–extracellular matrix (ECM) mimicry. The study is concluded with a discussion of the potential for in vivo applications of SLBs. Abstract : Supported lipid bilayers (SLBs) have great potential as a biomimetic cell interface. Their use as a cell membrane mimic has evolved into a platform for bioanalysis and the study of cell–cell and cell–extracellular matrix interactions. The fabrication, modification, analysis, in vitro and in vivo applications of SLBs are reviewed.